Leptin Receptor Expressing Neurons in the Substantia Nigra Regulate Locomotion, and in The Ventral Tegmental Area Motivation and Feeding - de Vrind, Véronne A. J.; van ‘t Sant, Lisanne J.; Rozeboom, Annemieke; Luijendijk-Berg, Mieneke C. M.; Omrani, Azar; Adan, Roger A. H. (Frontiers in Endocrinology, 2021)
Leptin is an anorexigenic hormone, important in the regulation of body weight. Leptin plays a role in food reward, feeding, locomotion and anxiety. Leptin receptors (LepR) are expressed in many brain areas, including the midbrain. In most studies that target the midbrain, either all LepR neurons of the midbrain or those of the ventral tegmental area (VTA) were targeted, but the role of substantia nigra (SN) LepR neurons has not been investigated. These studies have reported contradicting results regarding motivational behaviour for food reward, feeding and locomotion. Since not all midbrain LepR mediated behaviours can be explained by LepR neurons in the VTA alone, we hypothesized that SN LepR neurons may provide further insight. We first characterized SN LepR and VTA LepR expression, which revealed LepR expression mainly on DA neurons. To further understand the role of midbrain LepR neurons in body weight regulation, we chemogenetically activated VTA LepR or SN LepR neurons in LepR-cre mice and tested for motivational behaviour, feeding and locomotion. Activation of VTA LepR neurons in food restricted mice decreased motivation for food reward (p=0.032) and food intake (p=0.020), but not locomotion. In contrast, activation of SN LepR neurons in food restricted mice decreased locomotion (p=0.025), but not motivation for food reward or food intake. Our results provide evidence that VTA LepR and SN LepR neurons serve different functions, i.e. activation of VTA LepR neurons modulated motivation for food reward and feeding, while SN LepR neurons modulated locomotor activity.